(untitled) (Chiang Mai, 1997)
Participans introductions, presentation of the broad overview of key environmental impact assessment issues in urban development and management in Thailand. Introduction to key contemporary urban environmental management problems and issues and how EIA and planning and management tools can contribute to more sustainable forms of urban development,...
Keywords: Urban development,Environmental impact analysis,Air,Phát triển nông thôn; Congresses,Congresses,Pollution,Tài liệu hội nghị, hội thảo